STRATEGI KONVERGENSI MEDIA DALAM KONTEN HIBURAN ANTV - Nugroho, Aris; Simangunsong, Benedictus Arnold (Master of Communication Science Program, Universitas Diponegoro, 2024)
The presence of new digital-based media has pushed a shift in media consumption patterns in society in obtaining information and content in entertainment programs, which is a challenge for ANTV in the media indutry competition. This is what is referred to as media convergence, namely the merger between conventional media and new media. It is important to see how the mass media does not only carry out the information function in reporting, but also has an entertainment function, especially in television media. By using a qualitative approach with the case study method, this article attempts to reveal the uniqueness and special specifications related to the media convergence strategy in entertainment content at ANTV, through in-depth interviews and observation and documentation. The results of this study provide an illustration that media convergence in entertainment content at ANTV is carried out based on planning, implementation, and evaluation at each stage across promotion, content cloning, coopetition, content sharing and full convergence. Strategic steps in implementing ANTV's media convergence strategy refer to media integration in entertainment content, co-creation between TV and digital media, while also addressing the challenge of audience fragmentation and taking advantage of opportunities for ANTV to monetize new inventory.